Assessing stress restorative potential of plant species richness and plant landscape types of pocket parks: The mediating role of aesthetic quality - Yu Wang; Filzani Illia Ibrahim; Junlin Chang; Siti Norzaini Zainal Abidin (PLoS ONE, 2026)
The issue of stress among urban residents is becoming increasingly serious, affecting both physical and mental health in cities in China. Pocket parks serve as essential green spaces for people’s well-being in high-density urban environments. However, limited empirical research has examined how plant landscape components support stress recovery among urban residents, particularly in the context of pocket parks in China. This study investigated the effects of plant species richness and plant landscape types on stress recovery, with a focus on the mediating role of perceived aesthetic quality. A pre-test and post-test design were conducted in six selected pocket parks with different landscape characteristics using questionnaire surveys. A total of 605 urban residents were recruited using a random sampling method at different sites. The results indicated that medium plant species richness (t = −10.502, p < 0.01) and lawn landscape types (t = −12.006, p < 0.01) produced the most significant stress recovery effects. Furthermore, perceived aesthetic quality was found to partially mediate the relationship between plant landscape components and stress recovery. The findings of this study contribute to plant landscape research by providing empirical evidence to understand the effects of plant species richness, landscape type, and aesthetic perception on stress recovery in the context of pocket park in China, which is unexplored in past literature.